2023
DOI: 10.1021/acs.biomac.3c00053
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Identification of Lignin–Carbohydrate Complexes in Pre-hydrolysis Liquors

Abstract: The lignin−carbohydrate complexes (LCCs) typically present in the liquors produced in the pre-hydrolysis of biomass cause severe difficulties in downstream fractionation. To address this issue, a series of LCC samples were accessed from solutions obtained from the pre-hydrolysis of extractive-free pine wood meal (H-LCC) and compared with LCC obtained from the corresponding residues (B-LCC). Chromatographic and spectroscopic techniques revealed that 8.2% of the lignins were degraded at 160 °C, resulting from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Mango vinegar had the highest scavenging rate of ABTS free radicals up to 83.28 ± 0.76%. It was probably because the polyphenols in fruit vinegar had hydroxyl groups, which can combine with unstable molecules to generate stable substances and finally achieved anti-oxidation effect ( Brglez Mojzer, Knez Hrnčič, Škerget, Knez, & Bren, 2016 , Feng et al, 2023 ). In terms of comprehensive antioxidant indicators, the scavenging ability of different free radicals was different, which may be caused by the different types and contents of polyphenols in different fruit vinegars ( Olszowy, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mango vinegar had the highest scavenging rate of ABTS free radicals up to 83.28 ± 0.76%. It was probably because the polyphenols in fruit vinegar had hydroxyl groups, which can combine with unstable molecules to generate stable substances and finally achieved anti-oxidation effect ( Brglez Mojzer, Knez Hrnčič, Škerget, Knez, & Bren, 2016 , Feng et al, 2023 ). In terms of comprehensive antioxidant indicators, the scavenging ability of different free radicals was different, which may be caused by the different types and contents of polyphenols in different fruit vinegars ( Olszowy, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…After alkaline pretreatment, the lignin-rich black liquor generally requires solid-liquid separation before subsequent saccharification and utilization [86]. Inhibitors in the sugar solution, besides unwashed components of black liquor, mainly include lignin fragments deposited on celluloses and LCC (lignin-carbohydrate complexes) released from the fragmented cellulose [87,88]. The effective utilization of the separated lignin is the key to the economic viability of the entire biorefinery process.…”
Section: Alkaline Pretreatmentmentioning
confidence: 99%
“…Additionally, lotus procyanidins improved the water holding capacity of rice starch, hindering the recrystallization. Lotus procyanidins also formed a weak gel structure with rice starch, inhibiting the early retrogradation of starch to some extent. , …”
Section: Interaction Of Lotus Procyanidins With Other Nutrient Compon...mentioning
confidence: 99%
“…Lotus procyanidins also formed a weak gel structure with rice starch, inhibiting the early retrogradation of starch to some extent. 119,120 In addition, procyanidin−chitosan complexes have been shown to enhance the bioactivity of procyanidins. Ding et al found that procyanidin−chitosan complexes have good thermal and gastrointestinal digestive stability, improving the stability and bioavailability of procyanidins in gastrointestinal digestion.…”
Section: Interaction Of Lotus Procyanidins Withmentioning
confidence: 99%